Cognition as a Driving Factor for Mobile Phone Technology Use by Public University Students in Nairobi, Kenya - Wasiaya, O. C. (Archives of Business Research, 2023)
This paper examined cognition as a driving factor for mobile phone technology use by public university undergraduate students in Nairobi, Kenya. The objective of the study was: to examine the drive of cognition on undergraduate university students’ use of mobile phones. The research used the uses and gratifications theory and media technological determinism theory. The target population was 246,871 students in public universities in Nairobi, Kenya. The research design was quantitative. Findings indicated there was a correlation between extent of mobile phone technology use and cognition activities among undergraduate universities students. The research concluded that the more the need for cognition, the more the need for mobile phone technology use among university students. The research recommends to software developers that they could develop a specific mobile phone software for university students to use for cognition activities.